A Systematic Review and Meta-Analysis of Comparing Drainage Alone versus Drainage with Primary Fistula Treatment for the Perianal Abscess in Children - Sun, Yanting; Hao, Shuang; Zhang, Xi; Liang, Hongtao; Yao, Yibo; Lu, Jingen; Wang, Chen (European Journal of Pediatric Surgery, 2023)
This systematic review and meta-analysis of nonrandomized studies (NRSs) aimed to evaluate the clinical efficacy and safety of two types of surgical interventions (respectively drainage alone and drainage with primary fistula treatment) for perianal abscesses (PAs) in children. Studies from 1992 to July 2022 were searched in 10 electronic databases. All relevant NRSs with available data which compared surgical drainage with or without primary fistula treatment were included. Patients with underlying diseases which led to abscess formation were excluded. The Newcastle-Ottawa Scale was used to assess the risk of bias and quality of the included studies. The outcomes were the healing rate, fistula formation rate, fecal incontinence, and wound healing duration. A total of 16 articles with 1,262 patients were considered suitable for the final meta-analysis. Primary fistula treatment was associated with a significantly higher healing rate when compared with incision and drainage alone (odds ratio [OR]: 5.76, 95% confidence interval [CI]: 4.04–8.22). This aggressive procedure for PA resulted in an 86% reduction in the fistula formation rate (OR: 0.14, 95% CI: 0.06–0.32). Limited data showed patients who underwent primary fistula treatment have a minor effect on postoperative fecal incontinence. Primary fistula treatment demonstrates a better clinical efficacy in promoting the healing rate and decreasing the formation of fistulas in PAs in children. The available evidence for a minor impact on anal function after this intervention is less strong.
Keywords: systematic review; meta-analysis; perianal abscess; children; primary fistula treatment